2014
DOI: 10.1111/obr.12214
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth and risk of type 1 and type 2 diabetes: systematic review and meta‐analysis

Abstract: Preterm birth is suggested to play an important role in the development of diabetes. However, results have been inconsistent. We conducted a systematic review and meta-analysis to clarify the relationship between preterm birth and type 1 and type 2 diabetes. PubMed, Embase and ISI Web of Science were searched. A total of 18 studies (including 2,176,480 participants and 22,073 cases) for type 1 diabetes and five studies (including 31,478 participants and 1,898 cases) for type 2 diabetes were included in the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 41 publications
5
84
2
1
Order By: Relevance
“…It has been hypothesized that the effect of preterm and early-term birth on the risk of type 1 diabetes may be related to fetal growth restriction (7). Our data, however, do not support this hypothesis, as the association was unchanged when SGA children were excluded from the analysis.…”
Section: Potential Mechanismscontrasting
confidence: 57%
See 1 more Smart Citation
“…It has been hypothesized that the effect of preterm and early-term birth on the risk of type 1 diabetes may be related to fetal growth restriction (7). Our data, however, do not support this hypothesis, as the association was unchanged when SGA children were excluded from the analysis.…”
Section: Potential Mechanismscontrasting
confidence: 57%
“…In a recent meta-analysis of 14 case-control studies and four cohort studies, preterm birth (gestational age ,37 weeks) was found to increase the risk of type 1 diabetes by 18% (7). The authors highlighted several limitations in the literature such as a lack of consistent adjustment for important confounders.…”
mentioning
confidence: 99%
“…In contrast to our results, a meta-analysis, including a total of 18 studies for type I diabetes and 5 studies for type II diabetes, suggested that preterm birth was a significant and independent risk factor for both type I and type II diabetes (22). Finally, our data suggested that a premature birth plays a preventive role in becoming overweight or obese.…”
Section: Discussioncontrasting
confidence: 99%
“…While children born preterm were associated with increased incidence of diabetes, cardiovascular disease, respiratory disease, and neurological and psychiatric disorders in their adulthood life [3][4][5][6][7], one intriguing observation was about the prevalence of the childhood leukemia. Given the increasing number of children surviving preterm birth [29], any potential causal association between preterm birth and childhood leukemia could have a profound impact on public health issues.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, low gestational age at birth has been recognized as a crucial long term risk factor for multiple non-communicable diseases. A growing body of evidence has demonstrated that preterm birth infants are at a higher risk of developing diabetes, cardiovascular disease, respiratory disease, and neurological and psychiatric disorders in their adult life [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%